Une tentative d’histoire de la ville ibadite de Sadrāta - Virginie Prevost (Mélanges de la Casa de Velázquez)
The history of the town of Sadrāta is difficult to trace, as most documents where it is mentioned refer to it by the general term Ouargla.Contrary to what is generally believed, Sadrāta was not foundedex nihiloin the early 10th century by the last Rustumid Imam following his expulsion from Tahert by the Fatimids.Known by the name of Isedraten, by that time it was the most important oasis in the Ouargla region.Grown wealthy through trade with bilād al-Sūdān, it enjoyed its heyday in the10th century under the rule of the Ibadi chief Abū Ṣāliḥ Ǧannūn ibn Īmriyān.Sadrāta was destroyed for the first time by the Ḥammādid army around 1075, then utterly devastated by the rebel Yaḥyā ibn Ġāniya about 1229. The present-day Ouargla then became the definitive centre of the region.